Penataan Pemukiman Kampung Pajalah – Salamae Kabupaten Tolitoli - Dwi Purnomo (Formosa Journal of Social Sciences (FJSS), 2022)
The growth and development of the urban population that is not accompanied by an increase in people's income, so that it has an impact on the fulfillment of housing facilities that are less suitable for habitation. This condition occurs in Tolitoli Regency such as in Pajalah - Salamae Village where most of the people work in the informal sector, so there has been a decrease in the quality of the residential environment. This can be seen from the density of buildings / housing which is quite high and the placement is irregular, the condition of the housing is less suitable / does not meet the requirements for a healthy house. The purpose of this study was to obtain a formula for the design concept of the arrangement of residential buildings in the Kampung Pajalah - Salamae area based on environmental conditions by adhering to architectural principles and healthy housing requirements. The method used in planning is the Deductive Method where the discussion begins with Studies that are general in nature are then included in specific studies related to the existing conditions of settlements in Pajalah-Salamae village and their environmental facilities. The residential area of ​​Kampung Pajalah – Salamae is generally dominated by residents who work in the informal sector or who make a living as traders who are classified as low-income communities, 88 units of permanent buildings, 132 semi-permanent and 345 emergency units, residential neighborhoods in village settlement areas. Pajalah-Salamae is dominated by the condition of the building on stilts with the distance between the buildings very close / close together, so that the ventilation and lighting are inadequate, and the density of the building is quite high.